ОРЧИН ҮЕИЙН МОНГОЛЫН УРАН ЗОХИОЛ ДАХ ГАЗАР УСНЫ НЭРИЙН СУДАЛГААНЫ АСУУДАЛД - Ж.Бат-Ирээдүй (Acta Mongolica, 2014)
Toponym is the general term for any place or geographical entity. The toponymys are both the real names and the geographical names in the Modern Mongolian literature. They are related to the history of literature because we can find out a lot of its sources. We may conclude that these names are best-known places for authors. We can know a lot of things and the sources , because toponyms contain types of information. These are the one component of the languages.